2020
DOI: 10.1039/d0ra02454f
|View full text |Cite
|
Sign up to set email alerts
|

g-C3N4 synthesized from NH4SCN in a H2 atmosphere as a high performance photocatalyst for blue light-driven degradation of rhodamine B

Abstract: Graphitic carbon nitride (g-C3N4) was prepared by a simple thermal polymerization method in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The isotherms curves of materials display the typical type IV isotherms and type H4 hysteresis loops, proving the formation of mesopores in the obtained samples. Each isotherm does not have clear saturated adsorption platforms, which indicates a very irregular pore structure [ 11 ]. The results revealed that annealing in the H 2 atmosphere caused an increase in specific surface area (SSA), total pore volume, and average pore diameter.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The isotherms curves of materials display the typical type IV isotherms and type H4 hysteresis loops, proving the formation of mesopores in the obtained samples. Each isotherm does not have clear saturated adsorption platforms, which indicates a very irregular pore structure [ 11 ]. The results revealed that annealing in the H 2 atmosphere caused an increase in specific surface area (SSA), total pore volume, and average pore diameter.…”
Section: Resultsmentioning
confidence: 99%
“…The C 1s region includes three peaks. Specifically, the peak at 284 eV belongs to a special sp 2 C–C bond in the CN from g-C 3 N 4 [ 11 ]. The peak at 286.5 eV is attributed to the C atom on the aromatic ring connected to NH x [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations